International migration of older Poles - Dorota Kałuża-Kopias (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The aim of this study is to identify the scale of Polish emigration of elderly residents in the twenty-first century. At the outset presented in the literature developed concepts explaining the mechanisms of migration of seniors. Analyzing the actual movement of seniors, the focus was mostly on the scale of emigration, and the main directions of movements. The analysis was based on data on permanent emigration from the country in the years 2002-2013 are available on the Central Statistical Office. The result of the analysis indicate that older Poles are small, relatively stable in recent years, the proportion of immigrants. Migrants seniors are most often those who are married, characterized by a low level of education.